EDUCATIONART FESTIVAL : PAMERAN PENDIDIKAN SENI SEBAGAI PROYEK AKHIR MATA KULIAH PENDIDIKAN DAN KETERAMPILAN MAHASISWA PGSD FKIP UNIVERSITAS SARI MUTIARA INDONESIA - Setiawati, Nanda Ayu; Ismail, Putri Roka; Hutagaol, Robinson; Hajar, Ibnu (Universitas Negeri Medan, 2025)
This study aims to explore the learning experiences of students of the Elementary School Teacher Education Study Program (PGSD) of Sari Mutiara Indonesia University through their involvement in art education exhibition activities as a final project for the course. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation. The results of the study indicate that art exhibitions function as effective learning media, allowing students to creatively integrate theory with practice. This activity encourages the development of pedagogical competence, collaborative skills, and self-reflection. Students experienced an increase in their understanding of art-based learning, strengthening soft skills, and the ability to design contextual and meaningful teaching media. These findings indicate that art education exhibitions can be used as an innovative learning approach in teacher education, especially to form prospective educators who are adaptive, creative, and reflective.